Situation Report: Romania, 16 June 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reaction to Middle East, Manescu in Belgrade Ceausescu Touring Brasov Region Economic Relations with the GFR Privately Owned Apartments Experimental Organization of Trade Units Development of Servicing in Rural Areas New Management Center in Bucharest Miscellaneous